What happened among Japanese children from school closure due to COVID-19 after school re-opening? Changes in sleep habits and dietary intake - Minami Sugimoto; Kentaro Murakami; Satoshi Sasaki (Journal of Nutritional Science, 2023)
The present study aimed to (1) examine the changes in sleep habits and dietary intake among school-aged children after the school re-opening from a 3-month closure (without school lunch) due to the COVID-19 pandemic, and (2) examine whether the changes differ between those with different temporal patterns of sleep and eating during school closure, namely, ‘Very early’, ‘Early’, ‘Late’ and ‘Very late’. The latter patterns were characterised by later timings of wake up, breakfast and lunch. Questionnaires were answered twice by 4084 children (aged 8–15 years), themselves and/or their parents: first in June 2020 (for assessing lifestyle during school closure) and second, from July 2020 to February 2021 (for assessing lifestyle after school opening). After school re-opening, the participants’ wake-up time became an hour earlier (95 % CI 1⋅0, 1⋅1) and sleep duration got 0⋅94 h shorter (95 % CI 0⋅91, 0⋅97) than during school closure. An increase in dietary intake was observed for thiamine, vitamin B6, potassium, fruits and dairy products, and a decrease was observed for sugars (as foods) and confectioneries and sweetened beverages, despite small effect sizes (Cohen's d: 0⋅20–0⋅30). Significant changes in wake-up time, sleep duration and sweetened beverage intake were observed among children with the latter temporal patterns. Thus, children wake up earlier and sleep for shorter durations after school re-opening than during school closure; however, changes in dietary intake were generally insignificant. Dietary intake among school-aged children in Japan during school closure (without school lunch) might not be worse than that during school days with universal school lunch.